ANALISIS STEAM MENGGUNAKAN LOOSE PARTS DALAM MENGEMBANGKAN BERPIKIR KRITIS ANAK USIA 5–6 TAHUN DI RA DIAN INSANI - Nurul Fitria Kumala Dewi; Larasati Wisnu Putri Lestari; Ratu Rahmawati Putri; Siti Soleha (Pedagogi: Jurnal Ilmiah Pendidikan, 2026)
STEAM based learning using loose parts media is an effective approach to stimulate the development of critical thinking in early childhood. This descriptive qualitative study aims to analyze the implementation of STEAM at RA Dian Insani and its contribution to the development of critical thinking in children aged 5-6 years. Data were collected through observation, interviews, and documentation using instruments based on critical thinking indicators. The results of the study indicate that STEAM activities in the natural materials center, preparation center, and art center enable children to explore the stages of thinking from LOTS to HOTS. Teachers play an important role as facilitators who provide exploratory and meaningful learning experiences. Based on these findings, STEAM learning using loose parts media has been proven to develop children's critical thinking, as children demonstrate the ability to analyze, evaluate, and create through the use of various loose parts materials, both natural and artificial. This study emphasizes the importance of integrative, contextual learning designs that are centered on children's direct experiences.